A preliminary investigation of an Ancient North Arabian invocation from the Madaba region of central Jordan - Hayajneh, Hani (Proceedings of the Seminar for Arabian Studies, 2018)
This paper will edit and discuss two hitherto unpublished Ancient North Arabian (ANA) inscriptions from the Madaba region of central Jordan. They were found during the surveys of the Wādī al-Thamad Project in northern Moab (TT-5-WT Site WT-48) under the direction of Prof. M. Daviau. The inscriptions (consisting of one line and twenty lines respectively) are carved in the Hismaic script on a horizontal shelf of bedrock near a spillway in a curve of Wādī al-Thamad, which flows south-west into Wādī Mūjib. A decipherment of the inscriptions based on fresh photographs and photogrammetry is provided.